Probable association of acute pancreatitis with dicyclomine - Ahmad Kaako (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Kaako A. Probable association of acute pancreatitis with dicyclomine. Turk J Gastroenterol 2019; 30(3): 307-8.